KLASIFIKASI KETEPATAN KELULUSAN SISWA PADA SMK YADIKA 9 BINTARA JAYA KOTA BEKASI MENGGUNAKAN ALGORITMA C4.5 - Lestari, Sri; Dina, Bela (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Education is the learning of knowledge, skills, and habits of a group of people passed from one generation to the next through teaching, training, or research. SMK Yadika 9 Bintara Jaya Bekasi City is one of the private vocational schools, However, along the way, there are still problems that occur every year, namely the problem of the right number of student graduations and late. The number of students who graduate on time is an indicator of the effectiveness of a vocational school both public and private. SMK needs to detect the behavior of active students so that factors that cause students not to graduate on time can be seen. Data collection using techniques in the form of interviews and observations, in this study is related to systematic literature review to find predictive modeling using data mining classification methods. Data mining classification in determining the accuracy of student graduation with the CRISP-DM testing method. The results of this study resulted that the C4.5 algorithm is the most optimal method of performance in determining the graduation accuracy classification of students of SMK Yadika 9 Bintara Jaya Bekasi City.